Narracyjna i nienarracyjna koncepcja dyskursu literaturoznawczego - Ulicka, Danuta (Przestrzenie Teorii, 2007)
The article addresses questions of the relation between literary and literary science discourse which have been intensively discussed in poststructuralist reflection. As the author argues, their separation, accepted until the half of the century, in fact took place on the basis of pragmatic criteria (strongly connected with institutional division of work in the field of literary sciences), and not of a statement's formal characteristics or reference. What created the effect of stylistic, generic and compositional distinctness of speech genres inherent to literary science was only the prototype of literary science discourse shaped in result of their application and frequently confirmed in normative approaches, where it was formulated in terms of the categories of "truth" obliging science, as opposed to "fiction" distinguishing literature. Yet ineffaceable differences between literature and literary science are related to non-fictional and principally monosubjective characteristics of the discourse of the latter. Hence, in opposition to currently dominating narrativist interpretations, they can be by no means identified with respect to the "narrativeness" recognizable in both cases. While discussing these approaches on the basis of three chosen Polish works belonging to historioliterary prose, the author proposes to treat literary science discourse in categories applied to the description of a dramatic statement. For, what seems to be of paramount importance both in modernist and postmodernist phase, is the question of the author's subject's position and attitude towards the object of the statement and the relevant modalization of speech. A detailed analysis of their historical changeability remains, however, beyond the scope of the presented considerations.